The Influence of the Discovery Learning Model on the Learning Outcomes of Grade III Students in the Indonesian Language Subject at UPTD SDN 124398 Pematangsiantar - Siallagan, Febriani; Pasaribu, Eva; Siagian, Asister Fernando (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study aims to determine the effect of the Discovery Learning learning model on the learning outcomes of third-grade students in the Indonesian Language subject at the UPTD of SD Negeri 124398 Pematangsiantar in the 2025/2026 Academic Year. The study used a quantitative approach with a one-group pre-test post-test design. The subjects of the study were 20 students who were given an initial test (pre-test) and a final test (post-test). The research instrument was a multiple-choice test consisting of 20 questions that had been tested for validity and reliability. The results showed a significant increase in the average score of students from 59.25 in the pre-test to 84.75 in the post-test, with the number of completeness increasing from 7 to 19 students. The paired sample t-test produced a t-value of 7.216 with a significance of 0.000 (less than 0.05), so the alternative hypothesis was accepted. Thus, it can be concluded that the application of the Discovery Learning model has a positive and significant effect in improving the Indonesian language learning outcomes of grade III students at the school.